Analisis Pengendalian Kualitas Produk Midsole Dengan Metode Seven Tools Dan Failure Mode Effect Analysis Pada PT.XYZ - Paradika Rossadi; Sumiati Sumiati (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
PT. XYZ is a company operating in the shoe industry. In the midsole production process, defects such as burning defects, tear defects, bubble defects and dirty. The aim of this research is to determine the proportion of defects that most frequently occur and the factors that cause defects and to provide suggestions for improving the quality of the Midsole. The method used is Seven tools and Failure Mode Effect Analysis (FMEA). Seven tools include check sheets, statistics, histograms, Pareto diagrams, scatter diagrams, control charts, and fishbone diagrams. Then continue the FMEA analysis to get suggestions for corrective actions. Based on the results of Seven Tools research, it is known that the most dominant defects in the midsole are burnt (38%), then dirty (24.4%), bulging (20%), and torn (17.4%). 6%) ). Based on the results of the Failure Mode Effect Analysis (FMEA) research, it is known that the highest cause of problems with RPN 343 is uneven spraying of the Mold Release Agent. Suggestions for improvement that can be submitted are: Conduct training to workers on how to spray MRA according to standards and determine rest time limits so that the injection machine does not overheat.